Region and Cell Type Distribution of TCF4 in the Postnatal Mouse Brain - Hyojin Kim; Hyojin Kim; Noah C. Berens; Nicole E. Ochandarena; Benjamin D. Philpot; Benjamin D. Philpot; Benjamin D. Philpot (Frontiers Media S.A., 2020)
Transcription factor 4 is a class I basic helix-loop-helix transcription factor regulating gene expression. Altered TCF4 gene expression has been linked to non-syndromic intellectual disability, schizophrenia, and a severe neurodevelopmental disorder known as Pitt-Hopkins syndrome. An understanding of the cell types expressing TCF4 protein in the mouse brain is needed to help identify potential pathophysiological mechanisms and targets for therapeutic delivery in TCF4-linked disorders. Here we developed a novel green fluorescent protein reporter mouse to visualize TCF4-expressing cells throughout the brain. Using this TCF4 reporter mouse, we observed prominent expression of TCF4 in the pallial region and cerebellum of the postnatal brain. At the cellular level, both glutamatergic and GABAergic neurons express TCF4 in the cortex and hippocampus, while only a subset of GABAergic interneurons express TCF4 in the striatum. Among glial cell groups, TCF4 is present in astrocytes and immature and mature oligodendrocytes. In the cerebellum, cells in the granule and molecular layer express TCF4. Our findings greatly extend our knowledge of the spatiotemporal and cell type-specific expression patterns of TCF4 in the brain, and hence, lay the groundwork to better understand TCF4-linked neurological disorders. Any effort to restore TCF4 functions through small molecule or genetic therapies should target these brain regions and cell groups to best recapitulate TCF4 expression patterns.